Training of non-communicable disease risk factors monitoring cadres at posyandu buluhcina village, kampar regency - Suci Dewi, Armoni; Suyanto, Suyanto; Putri, Fachriani (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Based on Indonesian Ministry of Health Regulation Number 08 of 2019, health empowerment cadres are individuals selected by the community and trained to encourage community participation in the health sector. Given the importance of the cadres’ role, training is necessary to enhance their capacity, particularly in Posyandu Lansia (Elderly Integrated Service Posts). This community service activity aims to improve the knowledge and skills of cadres in monitoring NCD (non-communicable disease) risk factors at Posyandu Lansia. The training is also expected to help reduce the prevalence of NCDs in Buluhcina Village, Kampar Regency, a partner in this community service initiative. Furthermore, this activity can recommend further studies in formulating models for preventing NCD risk factors. The community service activity showed significant improvements in knowledge, as indicated by the average pre-test and post-test scores. The pre-test average was 35.7%, which increased to 81.5% in the post-test. Thus, it can be concluded that this community service activity positively impacted the knowledge of cadres and the elderly, resulting in an increased understanding of NCD risk factors